Moderate Hyperbilirubinemia Alters Neonatal Cardiorespiratory Control and Induces Inflammation in the Nucleus Tractus Solitarius - Specq, Marie-Laure; Bourgoin-Heck, Mélisande; Samson, Nathalie; Corbin, François; Gestreau, Christian; Richer, Maxime; Kadhim, Hazim; Praud, Jean-Paul (Frontiers in Physiology, 2016)
Hyperbilirubinemia (HB) occurs in 90% of preterm newborns. Moderate HB can induce acute neurological disorders while severe HB has been linked to a higher incidence of apneas of prematurity. The present study aimed to test the hypothesis that even moderate HB disrupts cardiorespiratory control in preterm lambs. Two groups of preterm lambs (born 14 days prior to term), namely control (n = 6) and HB (n = 5), were studied. At day 5 of life, moderate HB (150-250 µmol/L) was induced during 17h in the HB group after which cardiorespiratory control as well as laryngeal and pulmonary chemoreflexes were assessed during baseline recordings and during hypoxia. Recordings were repeated 72 hours after HB induction, just before euthanasia. In addition, neuropathological studies were performed to investigate for cerebral bilirubin deposition as well as for signs of glial reactivity in brainstem structures involved in cardiorespiratory control. Results revealed that sustained and moderate HB: i) decreased baseline respiratory rate and increased the time spent in apnea; ii) blunted the cardiorespiratory inhibition normally observed during both laryngeal and pulmonary chemoreflexes and iii) increased heart rate in response to acute hypoxia. These acute physiological changes were concurrent with an activation of Alzheimer type II astrocytes throughout the brain, including the brainstem. Concomitantly, bilirubin deposits were observed in the leptomeninges, but not in brain parenchyma. While most cardiorespiratory alterations returned to normal 72 hours after HB normalization, the expression of glial fibrillary acid protein (GFAP) and Ionized calcium binding adaptor molecule 1 (Iba1) was still increased within the nucleus tractus solitarius. In conclusion, moderate and sustained HB in preterm lambs induced cardiorespiratory alterations, the latter of which were associated with neurohistopathological changes. These changes are indicative of an inflammatory response in the brainstem neuroanatomical substrates involved in cardiorespiratory control.